CTNS Molecular Genetics Profile in a Portuguese Cystinosis Population - Ferreira, Filipa (2019)
Background: Cystinosis is a multisystemic autosomal recessive deficiency of the lysosomal membrane transporter protein (cystinosin) caused by mutations in CTNS gene. Objective : This study summarizes the Portuguese experience in the diagnosis and management of patients with this rare disease over the past few years and reports recurrent mutations in the CTNS gene . Methods : Unrelated patients from different pediatric and adult hospitals all over Portugal with non-nephrotic proteinuria, hypercalciuria, hypokalemia impaired proximal reabsorption of amino acids, glycosuria and hypophosphatemia, suggestive of a Fanconi syndrome and ocular problems, were studied. Intra-leukocyte cystine levels were determined and molecular analysis was performed, to determine the presence or absence of the 57-kb deletion in CTNS , followed by direct sequencing of the coding exons of CTNS . Results : From 1998 to 2017, twenty-one cystinotic patients were biochemically diagnosed. From the remaining seventeen (four deceased), eleven were studied for CTNS gene. Five out of eleven patients were homozygous for the 57-kb deletion (10/22; 45.5%), and other five were compound heterozygous for this variant (15/22; 68.2%). The other mutations found were p.Q128X (c.721 C>T; 2/22), p.S139F (c.755 C>T; 4/22) and c.18-21delGACT (p.T7FfsX7; 1/22). All of these seventeen cystinotic patients are in treatment. Approximately 84% are adults, 16% are young children, and 54.5% are kidney transplant recipient. Conclusions: The authors would like to emphasize the importance of first screening for the 57-kb deletion since it is very common in our population. This genetic study is the first in our country and it could be the basis for future genetic counseling in Portuguese population.